Inorganic Syntheses, 35. - Rauchfuss, Thomas (Inorganic syntheses., 2010)
The Inorganic Syntheses series provides all users of inorganic substances with detailed and foolproof procedures for the preparation of important and timely compounds.: Includes complete, up-to-date procedures involving important inorganic substances; Contains subject, contributor, and formula indexes.